Comunidade fitoplanctônica e variáveis limnológicas no Reservatório Rio Bonito - Rio Santa Maria da Vitória (Santa Maria de Jetibá - ES) - Rubim, Karine Toso (2006)
This search was realized in the Rio Bonito reservoir - Santa Maria da Vitória river, situated 60 km far from Vitória, in the city of Santa Maria de a Jetibá – ES (Brazil). This reservoir has area of the 2,2km2 , maximum lenght of 14 km, maximum volume of 26.350.103 m3 and takes the generation of electric energy as a principal finality. The main study’s objective was to verify both spatial and temporal changes on phytoplanktonic community of the Rio Bonito reservoir and to relate with abiotic variables. The samplings were carried out in two stations (E1 and E2) of reservoir’s lacustrine area, in three different deeps (sub-surface, eufotic zone, and afotic zone), with trimonthly periodicity, on july/2004 to april/2005. Were analysed: climatological variables, air and water temperature, pH, total alkalinity, dissolved oxygen, transparency, turbidity, ammoniacal nitrogen, nitrite, nitrate, ortophosfate, chlorophyll a, feofitin, total density and of phytoplankton Class, specific diversity and equitabilty, taxon’s wealths, abundant and dominant species, qualitative and quantitative analysis of the toxins produced by cyanobacteria (microcystin, cylindrospermopsin and saxitoxin) in seston’s samples. How about the qualitative composition of phytoplankton community 106 taxon’s were registered, the Chlorophyceae Class was the most representative about taxon’s wealth, on both stations of sampling. There happened an elevated variation of the total numerical density of phytoplankton community, oscillating of 7.022 cells/mL (E1- afotic zone - january/05) to 905.674 cells/mL (E1 - sub-surface - july/04). How about the density there was a quantitative domain of Cyanophyceae Class, in a percentage that varied from 83,8% to 99,9%, the dominant specie on the three initial sampling periods was Cylindrospermopisis raciborskii and on the last period Synechocystis sp. Seven abundant species were found, wich are: Cylindrospermopsis raciborskii, Synechocystis sp, Synechococcus sp, Monoraphidiopsis sp, Oscillatoria jasorvensis, Pseudoanabaena sp - of the Cyanophyceae Class e Ankistrodesmus sp of the Chlorophyceae Class. Low values of specific diversity and equitability were registered because of the domination of two species on the studied period. The biggest concentrations of chlorophyll a were registered in the sub-surface and eufotic zone, coinciding with the depths with larger total density of phytoplankton. The rainfall informations confered two distinct periods, one with lower tax of precipitation (july to october/04) and the other with a bigger tax of precipitation verified from november to may /05, with atypical rains on may. The highests mediums of total numerical density were registered on july/04, and the lowers values were found on april/05, month that suceeded the high tax of precipitation. The analysis of main components showed that positive correlation between total numerical density of phytoplankton, especially Cyanophyceae Class, pH, dissolved oxygen, chlorophyll a in contraposition to depth collection, the concentrations of nitrate and to diversity. None of the tested toxins (microcystin, cylindrospermopsin and saxitoxin) was detected in the samples of seston. Although the Rio Bonito reservoir has not been constructed with the purpose of public water supply, the river Santa Maria da Vitória is used to this finality in Grande Vitória’s region. This reservoir is an imminent danger, so the cyanobacteria blooming present in this ecosystem can be considered of inoculation to these microorganisms for the waters downstream from the reservoir, wich will reflect problems to water treatment stations and the public health, if present cyanobacterial strains producing cianotoxins. Before of these facts become essential the constant monitorament of cyanobacteria and cyanotoxins at this ecosystem.